Konsep Pendidikan Agama Islam Sebagai Manhaj Pengelolaan Taman Pendidikan Qur’an - Lumbesi, sahbudin (Sekolah Tinggi Agama Islam Babussalam Sula, 2022)
Islam is a guide in the life of the Muslim community in the world and prepares for life in the hereafter. How important the role of Islam is for the lives of Muslims, the internalization of religious values ​​in the life of every Muslim person becomes a necessity. Al-Qur'an Education Park (TPQ) has a strong legal entity foundation, as stated in Government Regulation no. 55 of 2007 article 24 paragraph 2 concerning Religious Education and Religious Education states that Al-Qur'an Education consists of Al-Qur'an Kindergarten (TKA/TKQ), Al-Qur'an Education Park (TPA/TPQ) , Ta'limulQur'an lil Aulad (TQA), and other similar forms. In Law No. 20 of 2003 concerning the National Education System that one of the characteristics of Indonesian people thatTo be able to study the Qur'an requires an effort and of course it has the educational values ​​of the Qur'an itself, through a continuous teaching and learning process so that the teaching and learning process can run effectively and efficiently.